Pengaruh Pemisahan Hak AliranKas dan Hak Kontrol terhadap Dividen - BALDRIC SIREGAR (The Indonesian Journal of Accounting Research, 2013)
The expropriation of minority shareholders by those of controlling shareholders is the main agency conflict in firms with concentrated ownership. The expropriation is obvious when cash flow and control rights are separated through pyramiding and cross-holdings. The ultimate ownership concept is used to identify the separation and investigate its implications on dividend. By using sample of firms listed in the Jakarta Stock Exchange for the period from 2000 to 2004, empirical evidence shows that cash flow and control rights do not go together but have different implications. The cash flow right concentration is an incentive to avoid expropriation. This can be seen from evidences of positive effects of cash flow rights on dividend. On the other hand, control right concentration is an incentive to generate private benefits through expropriation. This conclusion is supported by evidence of negative effects of control rights on dividend. When control rights exceed cash flow rights, the controlling shareholders have higher incentive to expropriate by participating in firm's management. The controlling shareholders' participation in management makes them more free to generate private benefits. The incentive, how ever is lower when a firm has the second controlling shareholder. The second controlling shareholder can mitigate the controlling shareholder's incentive to expropriate.